WATER RESOURCE INFRASTRUCTURE IMPLICATIONS OF A GREEN ECONOMY TRANSITION IN THE WESTERN CAPE PROVINCE OF SOUTH AFRICA: A SYSTEM DYNAMICS APPROACH - Pienaar, Aliza; Brent, Alan C; Musango, Josephine K; De Kock, Imke H (The South African Journal of Industrial Engineering, 2017)
The Western Cape Province government in South Africa has established the transition to a green economy as a high priority. The sustainable use of water resources has been identified as a critical necessity for such a green economy transition. The research summarised in this paper conceptualised the factors that relate to water resources, and that influence the transition to a green economy in the Western Cape Province. Subsequently, a system dynamics model was developed to evaluate the impact of key strategic interventions of the green economy transition. The results from the model show that the Province could possibly experience extreme water shortages in the near future if a business-as-usual scenario continues. However, with sufficient investment and effective management, the water demand of the Province can be met.